An International Comparison of Work Sharing Programs - Crowley, R.; Huth, E. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
This article draws together primarily unpublished information that provides comparative information with respect to North American and Western European experiences with work sharing.